Molecular cloning of AtRS4, a seed specific multifunctional RFO synthase/galactosylhydrolase in Arabidopsis thaliana - Gangl, Roman; Behmüller, Robert; Tenhaken, Raimund (Frontiers in Plant Science, 2015)
Stachyose is among the raffinose family oligosaccharides (RFOs) one of the major water-soluble carbohydrates next to sucrose in seeds of a number of plant species. Especially in leguminous seeds, e.g. chickpea, stachyose is reported as the major component. In contrast to their ambiguous potential as essential source of carbon for germination, RFOs are indigestible for humans and can contribute to diverse abdominal disorders. In the genome of Arabidopsis thaliana, six putative raffinose synthase genes are reported, whereas little is known about these putative raffinose synthases and their biochemical characteristics or their contribution to the RFO physiology in A. thaliana. In this paper, we report on the molecular cloning, functional expression in Escherichia coli and purification of recombinant AtRS4 from A. thaliana and the biochemical characterisation of the putative stachyose synthase (AtSTS, At4g01970) as a raffinose and high affinity stachyose synthase (Km for raffinose 259.2 ± 21.15 μM) as well as stachyose and galactinol specific galactosylhydrolase. A T-DNA insertional mutant in the AtRS4 gene was isolated. Only semi-quantitative PCR from WT siliques showed a specific transcriptional AtRS4 PCR product. Metabolite measurements in seeds of ΔAtRS4 mutant plants revealed a total loss of stachyose in ΔAtRS4 mutant seeds. We conclude that AtRS4 is the only stachyose synthase in the genome of A. thaliana that AtRS4 represents a key regulation mechanism in the RFO physiology of A. thaliana due to its multifunctional enzyme activity and that AtRS4 is possibly the second seed specific raffinose synthase beside AtRS5, which is responsible for Raf accumulation under abiotic stress.